PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE GROUP INVESTIGATION BERBANTUAN MEDIA VISUAL UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SD BANJAR JAWA 3 - Sagita Nggebu, Rindhy Anggreany; Kusmariyatni, Nyoman (Universitas Pendidikan Ganesha, 2018)
The purpose of this study was to improve the learning outcomes of natural science through the application of cooperative learning model type investigation group assisted visual media in grade 5 elementary scholl (SD) Negeri 3 Banjar Java . This research is a classroom action research conducted in two action cycles. The subject of this study was the 5th grade students of SDN 3 Banjar Java in the school year 2018/2019 as many as 32 students. Data collection of this result of learning science in this study was carried out by using essay-shaped test methods. Then the data is analyzed by using qualitative desktop descriptive and quantitative descriptive techniques.Â The research data shows that in the firstcycle the data of learning outcomes of IPA reached 74,06 % in the medium category and in the second cycle it reached 85,31 % in the high category. Thus, increasing science learning outcomes reached 11,25%. The result of this study indicate that cooperative learning model type investigation group assisted visual media can improve science learning outcomes for grade 5b students in semester 1 of 2018/2019 school year at SDN 3 banjar Java.Â Keywords: Cooperative Learning Model Type Investigation Group; Visual Media;Science Learning Outcomes